Limits and advantages of abdominal ultrasonography in children with acute appendicitis syndrome - Valentina Pastore; Raffaella Cocomazzi; Angela Basile; Marlena Pastore; Fabio Bartoli (Wolters Kluwer Medknow Publications, 2014)
Background: Graded compression ultrasonography (US) has become the most popular technique used in suspected appendicitis and in our prospective study, we have evaluated its contribution to the diagnosis of acute appendicitis during the period 2010-2013. Materials and Methods: Four hundred and eighty children underwent urgent abdominal suspected of having acute appendicitis. Patients were divided into operated groups; (220 patients) and non-operated (260 patients) the final diagnosis was established on histopathological findings in the first group and on the phone interview in the second one. US was the sole imaging modality in all the non-operated patients and in 203 out of 220 operated ones. Seven children in the operated group underwent CT, while a second US was performed in 10 patients. Results: Acute appendicitis was confirmed in 188 operated patients while no one in the non-operated group returned to the hospital or was operated for appendicitis. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 79%, 78%, 95%, 39% and 79%, respectively. Negative appendectomy and perforation rates were 14% and 8%. Seventeen children in the operated group required a second diagnostic imaging: 7 CTs and 10 USs. All the seven CTs were consistent with appendicitis and 6 out of 10 USs showed ecographic signs of appendicitis. Conclusion: Our results support routine US in all the children with suspected appendicitis because it helps in reducing negative appendectomy and perforation rate. Moreover, a negative US does not justify a subsequent and immediate CT because clinical re-evaluation and a second US can clarify the diagnosis.